Problém autonómie subjektu v Nussbaumovej teórii spôsobilostí. - FOLTIN, MARTIN (Filozofia, 2025)
This paper deals with autonomy in political philosophy and theories of justice. The starting point is a critique of traditional, abstract concepts of autonomy (stoicism, social contract theory), which, according to Martha C. Nussbaum, fail to adequately respond to real human vulnerability and inequality. It presents an alternative - the capabilities approach, which redefines autonomy as a set of real possibilities for leading a dignified life. The core is a critical analysis of Nussbaum's theory. It identifies three key tensions: between anti-paternalistic respect for choice and the normative character of her list of capabilities; between the individualistic basis and the necessity of collective action; and between the emphasis on external conditions and the insufficient elaboration of internal, psychological barriers to autonomy. The article assesses that Nussbaum's main contribution lies not in the final solution, but in the productive redefinition of the question of the conditions of human autonomy.